(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2024)
Farmers in Sub-Saharan Africa are often deterred from using fertilizers on their crops due to the high cost of inorganic fertilizers and the environmental strain associated with intensive agriculture, which relies heavily on inputs. However, a comprehensive understanding of how the integration of organic biomass, such as Senna siamea leafy biomass, and conventional fertilizers like NPK (15:15:15) impacts the growth and yield of specific crops like hot pepper is lacking. A field experiment was carried out at the Faculty of Renewable Natural Resources Demonstration Farm, KNUST-Kumasi, Ghana in 2023 to assess the effect of S. siamea leafy biomass and NPK (15:15:15) inorganic fertilizer on the growth and yield of hot pepper (Capsicum frutescens L.) in a randomized complete block design. Four treatments were used and allocated as T1 (Control), T2 (0.096kg of NPK), T3 (0.32063kg of S. siamea leafy biomass) and T4 (0.1532kg of S. siamea leafy biomass + 0.048kg of NPK). The treatments were replicated four times. The parameters investigated were; height, number of leaves, fruit yield and fruit dry weight. Treatments showed significant difference between them in the parameters investigated on, p?0.05. The combined application of S. siamea leafy biomass and NPK (15:15:15) fertilizer significantly increased the growth in height (42.75 cm), number of leaves (40.75), fruit yield (305291 fruits/ha) and dry fruit weight (484 kg/ha) of hot pepper compared to the sole application of the individual materials and the control, p?0.05. In terms of effect of these treatments, T4 [(0.1532 kg of S. siamea leafy biomass + 0.048 kg NPK (15:15:15)] favored the growth and yield of hot pepper the most, followed by the sole application of S. siamea leafy biomass T3 (0.32063 kg of S. siamea leafy biomass), sole NPK (0.09 kg of NPK) and then T1 (control) recording the lowest growth in height (19.32 cm), number of leaves (21.25), fruit yield (129693 fruits/ha) and fruit dry weight (115 kg/ha) of hot pepper. Therefore, the combined application of T4[(0.1532 kg of S. siamea leafy biomass + 0.048 kg NPK (15:15:15)] could be adopted by farmers as an economically fit fertilizer treatment for optimum hot pepper performance. Additionally, S. siamea leafy biomass might be adopted by hot pepper farmers as an alternative to inorganic in terms of cost and availability in sub-Saharan Africa.